(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses the use of modern pedagogical methods on the example of the "Case Study" method to increase the effectiveness of teaching the subject of Genetics. The use of cases makes the learning process interesting, multifaceted, creative, increasing motivation, the quality of education, interest in the subject, the ability to work independently, analyze, reason, draw the right conclusions when studying the topics of the discipline of Genetics.